Defending puts the anterior cruciate ligament at risk during soccer. A gender-based analysis - Brophy, R. H.; Stepan, J. G.; Silvers, H. J.; Mandelbaum, B. R. (Sports Health: A Multidisciplinary Approach, 2015)
Background: Soccer athletes are at risk for anterior cruciate ligament (ACL) injury. To date, there are limited studies on the mechanisms of ACL injuries in soccer athletes and no video-based analysis or sex-based comparison of these mechanisms.